THE ROLE OF SUBJECTIVE NORMS TO PREDICT EXPERIMENTAL BEHAVIOR THROUGH INTENTION OF SME OWNER IN JAKARTA - Selamat, Frangky (International Journal of Application on Economics and Business, 2023)
The crisis due to the pandemic has had a great negative impact on the survival of small and medium enterprises (SMEs) in various regions in Indonesia. Some gave up and closed their businesses. Some still survive and even continue to grow until now. For SMEs that persist, it is suspected that they have carried out a series of experiments so that their business survives. Experimental activities are carried out from modifying the product to changing the business model. This study was conducted to analyze the effect of subjective norms, namely family and closest friends, on the experimental behavior of SMEs mediated by intention. The theory of planned behavior is used to explain the relationship between these variables. The survey respondents are SME actors, totaling 35 people and running their businesses in Jakarta. The results showed that experimental behavior was influenced by intention, but subjective norms did not affect intention significantly. The presence of friends and family has a weak impact on SMEs to conduct a series of experiments on their business in order to maintain business sustainability.